Real-time cardiac metabolism assessed with hyperpolarized [1-(13)C]acetate in a large-animal model - Flori, Alessandra (Contrast Media Mol Imaging, 2014)
Dissolution-Dynamic Nuclear Polarization (dissolution-DNP) for Magnetic Resonance (MR) Spectroscopic Imaging has recently emerged as a novel technique for non invasive studies of the metabolic fate of biomolecules in vivo. Since acetate is the most abundant extra- and intra-cellular short-chain fatty acid, we focused on [1-(13)C]acetate as a promising candidate for a chemical probe to study myocardial metabolism of beating heart. Dissolution-DNP procedure of Na[1-(13)C]acetate for in vivo cardiac applications with 3T MR scanner was optimized in pigs during bolus injection of doses up to 3 mmoles. The Na[1-(13)C]acetate formulation was characterized by a liquid-state polarization of 14.2% and T(1Eff) in vivo of 17.6 ± 1.7 s. In vivo Na[1-(13)C]acetate kinetic displayed a bimodal shape: [1-(13)C]acetyl carnitine (AcC) was detected in a slice covering the cardiac volume, and the signal of (13)C-acetate and (13)C-AcC was modeled using the total Area Under the Curve (AUC) for kinetic analysis. A good correlation was found between the ratio AUC(AcC)/AUC(acetate) and the apparent kinetic constant of metabolic conversion k(AcC)/r(1) from [1-(13)C]acetate to [1-(13)C]AcC. Our study proved the feasibility and limitations of administration of large doses of hyperpolarized [1-(13)C]acetate with dissolution DNP to study by MR spectroscopy the myocardial conversion of [1-(13)C]acetate in [1-(13)C]acetyl-carnitine generated by acetyltransferase in healthy pigs.